2013
DOI: 10.1155/2013/203659
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydroxybenzoate Lithium Complexes in Inducing Apoptosis in HT-1080 Human Fibrosarcoma Cells

Abstract: There has been a growing interest in the beneficial effects of simple phenolic acids and their ability to exhibit various biological activities. The aim of this study was to assess in vitro biological activities of 2-, 3-, and 4-hydroxybenzoate lithium (HBLi) complexes on HT-1080 human fibrosarcoma cells by methods of using a metabolic activity assay, immunochemical and morphological techniques. Results showed that HBLi complexes exert their cytotoxic activities in a concentration-and chemical structuredepende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, the several attempts were carried out to design derivatives that focus on improving aspirin efficacy. Our previous research indicated that the designed new salicylate analogues reduced the effective dose of aspirin and induced apoptosis in different cell lines, including fibrosarcoma, breast cancer, and primary chronic lymphatic leukaemia (CLL) [3][4][5][6]. These compounds include hydroxybenzoate Na, Ca, and Zn, (Figure 1), 4-HBZn was the most effective anti-cancer agent [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the several attempts were carried out to design derivatives that focus on improving aspirin efficacy. Our previous research indicated that the designed new salicylate analogues reduced the effective dose of aspirin and induced apoptosis in different cell lines, including fibrosarcoma, breast cancer, and primary chronic lymphatic leukaemia (CLL) [3][4][5][6]. These compounds include hydroxybenzoate Na, Ca, and Zn, (Figure 1), 4-HBZn was the most effective anti-cancer agent [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research indicated that the designed new salicylate analogues reduced the effective dose of aspirin and induced apoptosis in different cell lines, including fibrosarcoma, breast cancer, and primary chronic lymphatic leukaemia (CLL) [3][4][5][6]. These compounds include hydroxybenzoate Na, Ca, and Zn, (Figure 1), 4-HBZn was the most effective anti-cancer agent [4,6]. In this respect, zinc 4-HBZn reduced cell viability, arrested cell cycle in G0/G1 and regulated apoptosis via intrinsic pathway [3,7].…”
Section: Introductionmentioning
confidence: 99%